Study on Braess’s Paradox in Supercritical Flow in Regenerative Cooling Channel - Zou Junbo, Liu Chaoyang, Li Xin, Zhang Jincheng, Wu Xiaomeng (Hangkong bingqi)
The regenerative cooling system based on hydrocarbon fuel is the key to breaking through the long-term reliable operation of scramjet engines. The local connections that may be caused by machining errors will change the flow distribution of the system, which will easily cause structural damage. Existing studies have found that the Brass’s paradox phenomenon of flow will occur in the micro-network channel under specific working conditions, that is, the system flow is lower when the channel network is locally connected than when it is not connected. This paper focuses on exploring whether Braess’s paradox will occur in the locally connected channel network under macro-scale conditions, focusing on the conditions and influencing factors of this phenomenon, and studying the influence of system flow changes on the heat transfer characteristics of thermal protection systems. First, based on the numerical simulation method, the existence of Braess’s paradox phenomenon is proved, that is, the total flow rate of the H-shaped channel in the open state of the connecting channel is smaller than the total flow rate in the closed state of the connecting channel under certain working conditions. Then, considering factors such as obstacle position, size, connection position, and width, the simulation results and the system flow rate of parallel cooling channels are compared and analyzed. On this basis, the law of Braess’s paradox phenomenon is summarized.